Role of Selective Histone Deacetylase 6 Inhibitor ACY-1215 in Cancer and Other Human Diseases - Li, Jianglei; Yu, Meihong; Fu, Shifeng; Liu, Deliang; Tan, Yuyong (Frontiers in Pharmacology, 2022)
The deacetylation process regulated by histone deacetylases (HDACs) plays an important role in human health and diseases. HDAC6 belongs to the class-IIb of HDACs family, which can not only modify histone modification, but also non-histone proteins located in the cytoplasm. HDAC6 plays a key role in tumors, neurological diseases, and inflammatory diseases. Therefore, the treatment targeting HDAC6 has become a promising new direction in recent years. ACY-1215 is the first orally available highly selective HDAC6 inhibitor, and its efficacy and therapeutic effect are being continuously verified. This article summarizes the research progress of ACY-1215 and the corresponding pathway, in order to guide the future clinical trials of ACY-1215 and more in-depth mechanism research.